Hydrogen generation mechanism of BH4− spontaneous hydrolysis: A sight from ab initio calculation. (28th December 2016) - Zhou, Yongquan; Fang, Chunhui; Fang, Yan; Zhu, Fayan; Liu, Hongyan; Ge, Haiwen
Abstract: Recognition of the reaction mechanism of hydrogen generation by borohydrides hydrolysis can provide effective help for optimizing the reaction condition and catalyst design. In the present work, the underlying mechanisms of BH 4 − spontaneous hydrolysis under water-deficiency (2 water molecules) and water-rich (4 water molecules) condition were elaborated by the second-order Møller-Plesset perturbation theory (MP2) at MP2/6-311++G(3df, 3pd) level of theory. The present theoretical calculations predicted that dihydrogen bonding plays an extremely important role in the process of BH 4 − hydrolysis, and H2 is formed by a hydridic B-H hydrogen and a protic OH hydrogen. The hydrogen generation mechanism of BH 4 − hydrolysis in water-rich condition may experience BH 4 − → BH 3 ( OH ) −, BH 3 ( OH ) − → BH 2 ( OH ) 2 −, BH 2 ( OH ) 2 − → BH ( OH ) 3 − and BH ( OH ) 3 − → B ( OH ) 4 − four steps. BH 4 − hydrolysis mechanism in water-deficiency condition includes four steps in two possible reaction pathways as the water molecules participate with the reaction in different steps. All those reaction pathways with the same first step ( BH 4 − → BH 3 ( OH ) − ) and it's the Rate Determining Step (RDS) of the whole reaction. BH 4 − spontaneous hydrolysis at neutral or weak alkaline should be in the acid-catalyzed mechanism.